Experimental Study of Artificial Solar Air Heater Using Trapezoidal Wave Plate - Lohdy Diana; Arrad Ghani Safitra; Muhammad Syarifuddin Firmansyah; Mishbaakhus Prana Zinedine (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2019)
A solar air heater is needed for the drying process, especially in Indonesia. It means the researches to produce a solar air heater that had high performance is necessary. This research analyses the performance of solar air heater using trapezoidal absorber plate with variation of folded angle 83˚, 85˚, and 87˚. The research carry out artificial experimentally using halogen lamp as a solar simulator. The working principle of solar air heating begins with an induction fan sucking air to enter through the honeycomb then flowing into the air heating duct. The process of heat transfer occurs in a halogen heat lamp passed by the transparent glass and then absorbed by the absorbent plate. This heat will heat the air flowing in the air heating pipe to be transmitted into the drying cupboard. The experiment used several variations of the mass airflow rate 0.022 until 0.051 kg/s and intensity 850, 900, dan 950 W/m2. Temperature measurement is carried out by installing a thermocouple at several points that have been determined. The best performance produced by the wave plate-shaped trapezoidal wave heaters 83˚ when I = 950 W/m2 air mass flow rate 0.022 kg/s with the temperature of the absorbent plate 87 ˚C, the temperature of the exit air 43.2 ˚C, the difference in the rise in air temperature 15.2 ˚C, and when I = 950 W/m2 air mass flow rate 0.051 kg/s the useful heat generated by the air heater 527 Watt, and thermal efficiency 96.8%.